AUTOMATED DIAGNOSIS OF MECHANICAL PARTS OF PASSENGER CARS IN THEIR NORMAL OPERATION - Dmytriiev, D. V. (Science and Transport Progress, 2005)
On an example «Automated diagnostic system» are submitted experience of application and prospect of development of the given concept of diagnosing of a mechanical part of the railway rolling-stock.